Pengaruh Teknik Pemberian Kapur terhadap Pertumbuhan dan Hasil Kedelai pada Lahan Kering Masam - Subandi, Subandi; Wijanarko, Andy (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2013)
Acidic upland intended for soybean development areas must be limed to improve its soil fertility. The targeted soil is the root zones around 30 cm depth for soybean to decrease the level of acidity. The study was carried out in Sukadana, East Lampung Province, to determine the effect of lime application technique to the growth and yield of soybean in acidic upland. The experiment was conducted for two years (2009 and 2010). The experiment in 2009 used randomized complete block design to study four rates of lime, based on the calculation to decrease the exchangeable Al to 20%. Two weeks after lime was incorporated into the soil, soybean (Wilis variety) was planted, and bassal fertilizer of 300 kg NPK/ha was applied. In the 2010 experiment, each previous treatment plot was divided into two plots of the same size: one was treated with no lime to study the effect of the lime residue, and the second plot was limed as maintenance at rate of 25% of lime applied in the 2009 experiment. Soybean (Anjasmoro Variety) was planted, with bassal fertilizer of 2,5 t chicken manure + 300 kg SP18 + 300 kg NPK + 50 kg urea + 50 kg KCl/ha. Soil tillage to a depth of 30 cm on the no limed plots had decreased the growth and grain yield of soybean compared to those of soil tillage to a depth of 15 cm. Liming at 15 and 30 cm to the uppermost soil layer in 2009 increased the growth and yield of soybean, however the yield was not yet optimum. In the 2010 experiment, soybean grew optimally, yielded 2.67 t and 2.71 t/ha for lime treatments of 15 and 30 cm soil depth, respectively. To obtain high yield of soybean in the acidic uplands, it is suggested to lime on to the uppermost 15 cm soil layer using rate of lime to decrease the exchangable Al to 20% in the first year, and applying an additional lime in the following year at 25% of the first year rate.